Systematic monitoring attack repulsion total detection (SMART) detection / Khairunnisa Halim Azman - Halim Azman, Khairunnisa (2011)
Nowadays, we commonly used internet connections in our daily life activities such as communicating with friends and families, paying bills, retrieve information, downloading software and so on. Even some of the organizations and company also used internet connections for business purposes such as communicate with client, exchanging document and etc. However, the activities that have been mentioned earlier may cause threats to intrude into user computer and run silently behind it. This situation may pose a problem to the user because the intruders can stealth the information in user computer such as password, company confidential data and other business documentation. Currently, an intrusion detection system (IDS) is an important component for protecting information resources. It is similar to burglar alarms in the physical world which it monitors for intrusions and alert designated parties when suspicious activity is detected. The main objective of this project is to implement this IDS technology in Sapura Secured Technology (SST) network so that the network administrator of SST will be alert if there have any threats that try to intrude into their network. To successfully achieve our objective, we followed the guideline that we set in the methodology as well as following the timeline that has been stated strictly. This system is hopefully can overcome the possible threat of current network at SST such as IP Spoofing and Virus Attack.